Perempuan Indonesia Dalam Pusaran Kekerasan dan Ancaman Femisida - Dinda Sabrina (CV. ULIL ALBAB CORP, 2024)
Patriarchal culture which places men in higher position than women becomes a catalyst for arbitrary actions against women. The aim of this research is to understand the concept of femicide, examine legal regulations when facing the issue of femicide and outline the challenges and efforts that can be made to break the cycle of violence against women and minimize the threat of femicide. In this research, the author uses a qualitative research method that focuses on analysis and is supported by explanations from related literature. Femicide is not yet fully recognized in Indonesia, although there have been cases of murder from year to year, but this is still classified as general crime. There are no legal regulations that explicitly mention femicide. The lack of documentation and data collection on femicide cases is challenge faced. The role of the government as a policy maker is very important to immediately integrate femicide into legislation. With strict programs and regulations, it is hoped that it can increase awareness of all elements of society so that Indonesian women or girls can live in peace without having to fear that they will enter the vortex of violence and the threat of femicide in the future.